Transplantation of donor hearts after circulatory or brain death in a rat model - Li, Shiliang; Loganathan, Sivakkanan; Korkmaz-İçöz, Sevil; Radovits, Tamás; Hegedűs, Péter; Zhou, Yan; Karck, Matthias; Szabó, Gábor (Journal of surgical research, 2015)
Heart transplantation represents the only curative treatment for end-stage heart failure. Presently, the donor pool is restricted to brain-dead donors. Based on the lack of suitable donors and the increasing number of patients, we investigated some molecular pathomechanisms of the potential use of hearts after circulatory determination of death (DCDD) in transplantation.
Available online 24 December 2014
Gesehen am 22.06.2020